ANALISIS PESAN DAKWAH DI MEDIA SOSIAL TERHADAP RELIGIUSITAS MASYARAKAT MUSLIM: PUTRI SUCIANTI - SUCIANTI, PUTRI (Qawwam : The Leader's Writing, 2023)
Social media is an alternative in conveying dakwah messages, so that not a few dakwah actors use the media as a means. The complexity of the media requires da'i to be involved in the world of media, from this social media of course is an effective da'wah communication in keeping pace with the times. Therefore, this literature review study aims to determine the effectiveness of da'wah messages on social media on the religiosity of the Muslim community. A further in-depth study of the effectiveness of da'wah media needs to be carried out, because of the rapid development and use of media. Furthermore, in the analysis process, this research uses a literature study method by collecting various sources from journals, articles, and books related to research variables. The results of this literature study indicate that the effectiveness of social media dakwah can be said to be effective if the frequency of the intensity of a person using the media then applies the content of the message conveyed related to the existing dakwah study.